Bedouins and Sedentaries today in al-‘Ulâ (Kingdom of Saudi Arabia): al-diyâr and al-Dîra in the rear-view mirror - Vincent Battesti; Léo Marty (Arabian Humanities)
The Saudi communities that make up the oasis of al-‘Ulâ (Saudi Arabia) display a unity cemented by their belonging to the kingdom, de facto excluding foreign workers, who are nevertheless essential to the local oasis economy. This unity under the royal seal is more proclaimed than it is felt and experienced by the inhabitants of the region. Local collective identities are nested, defined by allegiance to one group as much as by its distinction from the other group of the same nature. This principle of nested subdivision begins between Bedouin and Sedentary groups and continues within them. These first results of a rare ethnographic survey in the Kingdom of Saudi Arabia are intended to offer—before the completion of the project that supports them—an essential knowledge base so that the current development of al-‘Ulâ, led by the Royal Commission for AlUla (RCU) and its contractors, can be carried out while paying close attention to the social realities of the local population.